2008
DOI: 10.1002/jcu.20522
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic assessment of uterine and ovarian development in normal girls aged 1 to 12 years

Abstract: There is a continuous increase in size of internal female genitalia from early childhood until the onset of puberty. We have provided reference percentile charts of normal uterine length, uterine volume, and ovarian volume in girls aged 1-12 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
32
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 26 publications
10
32
2
Order By: Relevance
“…In our study, maximum TUL was found to be 4.5 cm in prepubertal girls and the cut-off value for TUL was 4 cm, where sensitivity of 53 % and specifi city of 55 % were considered to be cutoff levels in differentiating prepubertal and pubertal girls in our population. Our study is in agreement with other studies revealing similar results in other countries (5,6,13,15,19) .…”
Section: Discussionsupporting
confidence: 96%
“…In our study, maximum TUL was found to be 4.5 cm in prepubertal girls and the cut-off value for TUL was 4 cm, where sensitivity of 53 % and specifi city of 55 % were considered to be cutoff levels in differentiating prepubertal and pubertal girls in our population. Our study is in agreement with other studies revealing similar results in other countries (5,6,13,15,19) .…”
Section: Discussionsupporting
confidence: 96%
“…Comparison of our findings with their data is shown in Figure 1. Comparison with smaller studies analyzing data from girls up to 14 years shows similar results [11,14,17]. Not including our patient, we identified 17 other cases of 46, XX DSD, aromatase deficiency [5,9,[18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Discussionsupporting
confidence: 86%
“…Two patients had a calculable ovarian volume of 28.5 cm 3 and 7.2 cm 3 on preoperative ultrasound, which was significantly greater than the expected volumes of 1.8 cm 3 AE 0.8 and 2.6 cm 3 AE 0.9 for a 10-and 11-year-old, respectively. 15,16 Two other cases had measurements performed intraoperatively by the surgeon and were noted to be 4 Â 5 cm (or a maximal area of 16.0 cm 2 ) and 8 Â 9 cm (or maximal area of 57.6 cm 2 ). Interestingly, in all four cases the ultrasonographer or the surgeon commented on the contralateral ovary appearing polycystic and significantly enlarged.…”
Section: Resultsmentioning
confidence: 99%
“…12,17 Even in the adolescent girl who did not meet volume criteria for PCOS, her volume of 7.2 cm 3 was still significantly enlarged when compared to her age group, which has an average of 2.6 cm 3 AE 0.9. 16 Furthermore, in the one case where a wedge biopsy was performed, the ovary was noted to have extensive hilar fibrosis possibly due to an increase in ovarian stroma as seen in PCOS. 17 Also, when comparing the adult population, the only significantly enlarged contralateral ovary was noted in a woman with PCOS.…”
Section: Discussionmentioning
confidence: 97%